2020
DOI: 10.3390/cancers12103006
|View full text |Cite
|
Sign up to set email alerts
|

The Mismatch Repair System (MMR) in Head and Neck Carcinogenesis and Its Role in Modulating the Response to Immunotherapy: A Critical Review

Abstract: The mismatch repair (MMR) system has a major role in the detection and correction of DNA replication errors, resulting from DNA polymerase slippage or nucleotides misincorporation. Specific inherited/acquired alterations or epigenetic inactivation of MMR genes are associated with microsatellite instability (MSI): the loss of crucial function in repairing DNA alterations can promote carcinogenesis by favoring the accumulation of thousands of mutations in a broad spectrum of different anatomic sites such as colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“… 62 Nevertheless, detecting microsatellite alterations (either in the tumor or in the peri-tumoral area) might be of interest as an adjunct to prediction of the risk for recurrence and potentially the response of OSCC to immune checkpoint blockers. 63 Other studies analyzing gene expression 64 or specific patterns of DNA methylation 65 from SMs found that this information potentially predicted a higher risk of postoperative recurrence in patients with R0-clear margins.…”
Section: Predicting Postoperative Risk In Locally Advanced Tumorsmentioning
confidence: 99%
“… 62 Nevertheless, detecting microsatellite alterations (either in the tumor or in the peri-tumoral area) might be of interest as an adjunct to prediction of the risk for recurrence and potentially the response of OSCC to immune checkpoint blockers. 63 Other studies analyzing gene expression 64 or specific patterns of DNA methylation 65 from SMs found that this information potentially predicted a higher risk of postoperative recurrence in patients with R0-clear margins.…”
Section: Predicting Postoperative Risk In Locally Advanced Tumorsmentioning
confidence: 99%
“…In routine use, detection of MSI is done by IHC for MMR (mismatch repair) proteins or by DNA profiling. MSI-high is associated with the efficacy of PD-1 blockade in other tumor types [30]; however, the incidence of the MSI-high phenotype is very low in HNSCC and no data are available for using it in clinical practice [31].…”
Section: Microsatellite Instabilitymentioning
confidence: 99%
“…Because of their repetitive nature, these microsatellites are prone to DNA polymerase pausing and slippage during replication. In normal tissue, the mismatch repair (MMR) system usually corrects these errors [1]. However, this process may malfunction due to a constitutional or sporadic mutation in one of the repair proteins.…”
Section: Introductionmentioning
confidence: 99%